Effectiveness of home-based exercise for functional rehabilitation in older adults after hip fracture surgery: A systematic review and meta-analysis of randomized controlled trials. - Lijun Zhao; Xiaona Zhao; Bin Dong; Xiaobin Li (PLoS ONE)
This systematic review and meta-analysis was performed to assess effectiveness of home-based exercise compared with control interventions for functional rehabilitation in elderly patients after hip fracture surgery. Comprehensive literature search was performed on PubMed, EMBASE, Web of Science, Cochrane library, and Clinicaltrails.gov to identify eligible randomized controlled trials (RCTs). Standard mean difference (SMD) and risk ratio (RR) with 95% confidence interval (CI) was calculated. The certainty of evidence of each outcome was assessed by using Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. A total of 28 articles reporting 21 unique RCTs (n = 2470) were finally included. Compared with control interventions, home-based exercise significantly improved Berg balance scale (BBS, SMD = 0.28, 95%CI: 0.03 to 0.53, P = 0.030), timed-up-and-go test (TUG, SMD = -0.28, 95%CI: -0.50 to -0.07, P = 0.009), Short Fort-36 physical component score (SF-36 PCS, SMD = 0.49, 95%CI: 0.28 to 0.70, P<0.001), and knee extensor strength (SMD = 0.23, 95%CI: 0.09 to 0.37, P = 0.001). No significant improvement was observed in gait speed, 6-minute walking test, short physical performance battery performance (SPPB), activities of daily living (ADL), or fear of falling in the home exercise group. Risk of adverse events, including emergency department visits, hospital readmissions, and falls, did not differ between both groups. According to GRADE, the overall certainty of evidence was moderate for usual gait speed, SPPB, ADL, fear of falling, and SF-36 PCS, and was low or very low for the other outcomes. Our meta-analysis demonstrated home-based exercise had positive effect on physical function after hip fracture surgery. Home-based rehabilitation might be recommended for rehabilitation of fractured patients after hospital discharge.